2006
DOI: 10.1021/jf0608773
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antifungal Activity of Salvia macrochlamys and Salvia recognita Essential Oils

Abstract: Essential oils of Salvia macrochlamys and Salvia recognita were obtained by hydrodistillation of dried aerial parts and characterized by gas chromatography and gas chromatography-mass spectrometry. One hundred and twenty identified constituents representing 97.7% in S. macrochlamys and 96.4% in S. recognita were characterized, and 1,8-cineole, borneol, and camphor were identified as major components of the essential oils. The oils were evaluated for their antimalarial, antimicrobial, and antifungal activities.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 22 publications
(29 reference statements)
2
32
0
2
Order By: Relevance
“…In our previous paper (9) we reported that 1,8-cineole and α−pinene were also the most abundant constituents in the oil of endemic plant species S. brachyodon. Similar results were obtained with S. caespitosa (10), S.macrochlamys, S.recognita (11), S. cryptantha (12), S. clevelandii (13), S. aytachii (14), S. willeana, S. fruticosa and S. pomifera (15) The oil of S. ringens var. baldacciana.…”
Section: Resultssupporting
confidence: 81%
“…In our previous paper (9) we reported that 1,8-cineole and α−pinene were also the most abundant constituents in the oil of endemic plant species S. brachyodon. Similar results were obtained with S. caespitosa (10), S.macrochlamys, S.recognita (11), S. cryptantha (12), S. clevelandii (13), S. aytachii (14), S. willeana, S. fruticosa and S. pomifera (15) The oil of S. ringens var. baldacciana.…”
Section: Resultssupporting
confidence: 81%
“…The predominant compound of O2 is eucalyptol [33]. Besides this one, borneol, α-pinene and camphor were identified in O2 [34].…”
Section: Resultsmentioning
confidence: 99%
“…& C.A.Mey. were evaluated for their antimalarial activity against P. falciparum (IC 50 = 17 μg/mL and 12 μg/mL respectively on D6 and W2) (Tabanca et al, 2006). Three closely related South African species (Salvia stenophylla Burch.…”
Section: Lamiaceaementioning
confidence: 99%